Typology of defects in DEMO divertor target mockups. (24th November 2021) - Addab, Y; Richou, M; Ramaniraka, M; Vignal, N; Visca, E; Dose, G; Roccella, S; Greuner, H; Missirlian, M; You, J H
Abstract: We analyzed data from ultrasonic testing and infrared thermography non-destructive examinations performed on a subset of 25 small scale water-cooled target mockups of four target designs developed in the 2nd R&D phase of WPDIV. Examinations were performed before high heat flux tests for the 25 mockups and after high heat flux tests for 18 of them. The detected manufacturing defects are various in size and location. Widths of defects range from 0.2 to 12 mm, which is the entire block width. Angular sizes of defects range from few degrees to 360°. Defects having an angular size less than 50° or a width less than 4 mm are likely to be missed by infrared thermography examinations. After high heat flux tests at 20 MW m −2 up to 500 cycles, we noticed no significant evolution of pre-existing defects.